The Acquisition Of English By Traders At Tourist Resort: An Ethongraphic Study At Gili Trawangan Tourist Resort Of North Lombok‐NTB - Muslimin, Muslimin; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriah Aryatmi, M.Hum (2013)
The goal of this study is to describe the procedures of English acquisition supplied by the language seekers (traders) at Gili Trawangan Tourist Resort of North Lombok of NTB. The objectives was totally refers to the four questions; what are the types of input displayed by traders in GTTR?; What are the types of output displayed by traders at GTTR?; How is the social distance between traders and TL speakers?; and How is the psychological distance between traders and TL speakers? Specifically, the type of the inquiry research is a qualitative and the research approach utilized is the ethnographic study. In this term, the ethnographer has handled several steps as consists of; observation, documentation, formal interview, and informal interview. The primary data took from the key informant (traders), and the secondary data received from other adequateness ones through formal and informal interviews. The following words have represent the result of this exploration; first, there were five point of inputs tresses in that workfield names listening to music, attending to ticket information, reading banners, watching cinema, and attending foreigners' utterance. The second fact finding is types of output, where the output processed by the acquirer represented by; promoting, singing, greeting, telling information, and transaction. Third result is the Psychological distance. Actually, there are two main issues such as follow; the great psychological distance and the small psychological distance. The great psychological distance was signed by; language shock, cultural shock, less of motivation, the less of enclosure, etc. Moreover in the small psychological distance was represented by; the good of enclosure, the great activity interest, the high motivation, etc. As the final resultfinding was represented by the following major cases; first, the great social distance, and the second is the small social distance. In great social distance, the traders in GTTR have encircled by the several bad conditions such as; the lack of economic interest, the small of assimilation, etc. In contrast, the small social distance represented by; the great enclosures, the great economic interest, the lack of subordination and domination, etc.